Pendidikan Nilai pada Tradisi Keislaman Masyarakat Fafanlap Distrik Misool Selatan Kabupaten Raja Ampat - Boften, Sayed Arkam; Nur, Indria (Tarbiyah STAIN Sorong, 2018)
The Birthday of the Prophet Muhammad SAW was a tradition that developed in the Islamic community long after the Prophet Muhammad died. The people of Fafanlap Village consider maulid as something that is not merely a tradition but is a form of Islamic teachings that is ordered contextually. The problem in this research is how the implementation of the procession maulid carried out in the village of Fafanlap? And What are the values of education that can be seen from the tradition of maulids in the Fafanlap community?. This study intends to describe the implementation of the maulid ritual tradition in Fafanlap Village and identify the value education of the maulid tradition of the Fafanlap Village community. In this study, the authors used a type of qualitative research with a pedagogical approach and took location in Fafanlap Village. The focus of research on the tradition of the birthday of the Prophet Muhammad. The author's data source obtained through literature study, observation, and interview interviews of related parties such as community leaders, who the authors consider to understand the concept of maulid and the processes that occur in Fafanlap Village in Fafanlap Village, South Misool District, Raja Ampat Regency. The results of this study indicate that the maulid tradition procession carried out in Fafanlap Village is an activity carried out that does not require a long time, both in terms of preparation, implementation, and closure, but in the procession revealed various spiritual values. Although in the process of carrying out the tradition of maulid in Fafanlap village it is not quite time-consuming, it can be said to be very tiring. Due to the full night of the village community sitting together in the mosque eagerly, the solemnity of reading some of the books of maulid summarized in one book. They believe and believe the little effort they made in terms of expressing their expressions of gratitude in commemorating the birthday of the Prophet Muhammad SAW could be a manifestation of profits to them in the next life. The tradition of maulid in the Fafanlap village community, indirectly put aside a lot of various concepts of Islamic religious education which have been passed down from generation to generation intentionally, related to the values of faith, worship, and morals.